Improving energy efficiency for intelligent reflecting surface assisted PD-NOMA in EH relaying network - Hong Nguyen-Thi; Thuc Kieu-Xuan; Thang Le-Nhat; Anh Le-Thi (Journal of Information and Telecommunication)
This paper focuses on building a new power domain non-orthogonal multiple access (PD-NOMA) network with the assistance of an intelligent reflecting surface (IRS). In particular, our proposed system consists of a source communicating with some destinations via the help of an energy-harvesting (EH) relay network that employs an amplify–and–forward protocol and a power–splitting (PS) scheme for EH. Three relay selection strategies are investigated to highlight the effectiveness of our proposed IRS–assisted PD-NOMA network compared to the non-IRS system. The Rice channel is adopted to model both BS-Relay (Base Station) and Relay-IRS-Users transmission links. We also construct a Particle swarm optimization (PSO)-based program to optimize the EE depending on power allocation for NOMA users and phase shift of the IRS elements. To determine the efficiency of PSO, we consider two other techniques: Genetic Algorithm (GA) and Exhaustive Search (ES). Finally, we evaluate the proposed model's performance in different scenarios, such as the number of IRS elements and the number of relay nodes, the relaying selection strategies, and the transmit power at the BS. The numerical results show that the IRS has a significant advantage in improving the EE performance of the EH-Relaying PD-NOMA system.